Factores determinantes de la competitividad del ensamble de vehículos Plug-in EV&PHEV de pasajeros, 2013-2019 - Díaz Murillo, Josué Enrique (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The objective of this research is to analyze the main determinants of competitiveness in the market for electric vehicles (EV) and plug-in hybrids (PHEV) during the period 2013 to 2019. The determinants considered, based on empirical theory and evidence, are: Gross Domestic Product (GDP), Human Capital (EMP), investment (IED), Regional Demand (DEM) and Energy Intensity (ENINT). The analysis will be conducted using an economic model, specifically a panel data model, Additional tests are carried out to determine the stationarity of the variables such as the unit root test (Levin, Lin & Chi), randomized effects tests (Hausman), as well as tests of normality (Jarque-Bera) and tests of heteroscedasticity (Breusch-Pagan). The study concludes that: investment, gross domestic product, and regional demand have a positive and significant effect on the competitiveness of the assembly of EV&PHEV vehicles; while a negative relationship exists between Human Resources and Energy Intewnsity.

El objetivo de esta investigación es analizar los principales determinantes de la competitividad en el mercado de vehículos eléctricos (EV) e híbridos enchufables (PHEV) durante el período 2013 a 2019. Los determinantes considerados, basados en teoría empírica y evidencia, son: Producto Interno Bruto (PIB), Capital Humano (EMP), inversión (IED), Demanda Regional (DEM) e Intensidad Energética (ENINT). El análisis se realizará utilizando un modelo económico, específicamente un modelo de datos de panel. Se realizan pruebas adicionales para determinar la estacionariedad de las variables como la prueba de raíz unitaria (Levin, Lin & Chi), pruebas de efectos aleatorios (Hausman), como, así como pruebas de normalidad (Jarque-Bera) y pruebas de heterocedasticidad (Breusch-Pagan). El estudio concluye que: la inversión, el producto interno bruto y la demanda regional tienen un efecto positivo y significativo en la competitividad del ensamblaje de vehículos EV&PHEV; mientras que una relación negativa existe entre Recursos Humanos e Intensidad Energética.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Negocios Internacionales
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2023-0490; Vehículos eléctricos; Competitividad; Sostenibilidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16492